2020
DOI: 10.2147/ott.s228702
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brevilin A Inhibits STAT3 Signaling and Induces ROS-Dependent Apoptosis, Mitochondrial Stress and Endoplasmic Reticulum Stress in MCF-7 Breast Cancer Cells</p>

Abstract: Breast cancer is the most common malignancy among women across the globe. Despite concerted efforts to improve the prevailing treatment modalities, the overall prognosis of breast cancer remains unsatisfactory. Recently, antiproliferative activity of Brevilin A (Brv-A), a sesquiterpene lactone compound of Centipeda minima, has been unveiled in various cancer types. Here, we have explored anticancer activity of Brv-A in MCF-7 breast carcinoma cells by targeting various pathways. Materials and Methods: Cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 56 publications
5
35
0
Order By: Relevance
“…There are a variety of sources of ROS, such as NADPH oxidases (NOX), mitochondrial electron transport chain, nitric oxide synthases, cytochrome P450 reductase, and xanthine oxidase. Among them, NOX are the main source to generate ROS, and NOX isoforms have been found to be involved in apoptosis, autophagy, and cell cycle regulation in breast cancer cells [ 24 , 25 ]. To investigate whether Rh1-produced ROS are involved in NOX activity, MCF-7 cells were pretreated with the ROS scavenger, N-acetylcysteine (NAC), the nonspecific NOX inhibitor, diphenyleneiodonium (DPI), or the specific NOX2 inhibitor, apocynin (APO).…”
Section: Resultsmentioning
confidence: 99%
“…There are a variety of sources of ROS, such as NADPH oxidases (NOX), mitochondrial electron transport chain, nitric oxide synthases, cytochrome P450 reductase, and xanthine oxidase. Among them, NOX are the main source to generate ROS, and NOX isoforms have been found to be involved in apoptosis, autophagy, and cell cycle regulation in breast cancer cells [ 24 , 25 ]. To investigate whether Rh1-produced ROS are involved in NOX activity, MCF-7 cells were pretreated with the ROS scavenger, N-acetylcysteine (NAC), the nonspecific NOX inhibitor, diphenyleneiodonium (DPI), or the specific NOX2 inhibitor, apocynin (APO).…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia and low pH are some of the major attributes of tumor milieu, enhancing anoikis evasion and therapy resistance. Several studies have shown that the therapeutic potential of small molecules (such as salinomycin) induced ROS production in cancer cells to inhibit anoikis resistance, invasiveness, migration, and metastasis (62, 90,[196][197][198]. This suggested that unexplored drugs, which demonstrate their pharmacological targets by inducing oxidative stress capable of restricting AIG in cancer cells without affecting normal cells, may be considered for future therapies.…”
Section: Perspective On Therapy To Target Anoikis Resistancementioning
confidence: 99%
“…STAT3 had been reported to play a crucial role in suppressing ROS signaling to favor tumorigenesis [26,27]. Also, STAT3 activation had been reported in anchorage-independent cancer cells [21][22][23]28].…”
Section: Stat3 Regulates V-atpase Expression In Tumor Cells To Promote Anoikis Resistancementioning
confidence: 99%